(untitled) (Jurnal Bahasa, 2006)
The semantic study of a word could not be carried out objectively as in the study of phonology, morphology or syntax. Instead of it, semantic study of words are made reliable by using a good methodology. This paper is the application of Semantic Field Theory which is used to de-scribe the lexical aspects of selected verbs in the Brunei dialect for the purpose to see their similarities and differences with the equivalent verbs in Standard Malay. The selected verbs in Brunei dialect are those verbs that can be classified into two groups of homonyms; (i) verbs that de-note the ’actions of beatings ’ and (ii) verbs that denotes the ’actions of cleaning’. These selected verbs pertains only to the various actions within a household or in the house. The similarities and differences of the lexi-cal aspects of the selected verbs in the two languages being compared, will be highlighted by using [+],[–] and [-I] symbols. The lexical aspects which are similar prove the semantics equivalent that are shared to-gether and the differences of the lexical aspects found, clearly denote the variations of certain aspects of meaning between the two verbs be-ing compared. The analysis which is based on the Componential Analysis Methodology shows clearly that not a single verb of the selected verbs in Brunei dialect is synonymous with the verb in standard Malay. Although the semantics aspects of the verbs being compared are as such, yet a verb in Brunei dialect (or in other Malay dialects) could be taken as part of the lexicon of Bahasa Melayu Standard.